Effect of crystallization on the photovoltaic parameters and stability of perovskite solar cells. (1st May 2021) - Wali, Qamar; Iftikhar, Faiza Jan
Graphical abstract: Outstanding characteristics of perovskite materials/hybrid organic–inorganic perovskite solar cells in view of selling points. Highlights: TiO2 employed as a model surface for perovskite crystallization. Crystallinity effects on the device performance were discussed. Stability factors have been highlighted. Sources of degradation in perovskite solar cells are reviewed. Abstract: Perovskite solar cells (PSCs) constitute a class of devices with significantly high photovoltaic conversion efficiency (>25%) and cost-effective solution processability in which an organic–inorganic hybrid perovskite material is utilized for photovoltaic action. In PSCs, the organic–inorganic hybrid perovskite heterogeneously crystallizes either on a thin flat surface (~100 nm) or a few microns thick layer of mesoporous surface, which typically develop planar and mesoporous PSCs, respectively. Other PSC architectures are derived from the above two. This article reviews the device–property and materials–property correlations in the aforementioned two architectures. The charging mechanism and the role of each layer in these devices have been discussed to understand the basic characteristics of the employed perovskite materials, the charge transport behaviour in nanostructured metal oxide semiconductors, and the factors that affect charge mobility. Issues such as the influence of humidity, thermal stress, and hysteresis that influence the performance of these devices have been discussed, along with an insight into future directions in the subject area.